The Effect of Creating 3D Software Using (CoSpaces Edu) To Develop Coding Skills for Primary School Students - Alghamdi, Areej Abdullah Salem; Harboush, Layla Hamad; Mujallid, Amjaad Tariq (Journal of Educational and Psychological Sciences, 2023)
This study aimed to investigate the effect of creating 3D software i using CoSpaces Edu platform on developing coding skills for primary school students. In this study, semi-experimental method was used. The study sample included (31) female students in the sixth grade of primary school. They were divided into two experimental groups, according to the learning style. The first group represented the individual learning style, and contained (15) students. While the other group represented the cooperative learning style and had (16) students. In this study, the researchers prepared research tools consisting of a coding cognitive test and a product evaluation card. the results showed statistically significant differences in the post-test of the two experimental groups in favor of post-test. Also, there are statistically significant differences in the post-test in favor of the experimental group with a cooperative style. The study recommends taking advantage of the participatory virtual environments to develop coding skills and employing them in teaching coding to primary school students.
Keywords: Cospecies Edu; participatory virtual environments; coding skills